(untitled) (Experimental biology, 2023)
An increase in the amount of environmental pollution caused by different hazardous elements and anthropogenic pressure complicates and decreases Kazakhstan’s natural resources’ stable ecological state. According to the Republic of Kazakhstan’s bulletin on the state of the environment, the content of calcium and sodium nitrate and nitrite ions in water bodies grew by 13.5 and 7.5%, respectively, in the first half of 2022, indicating that their actual concentration exceeded the background class. At the same time, it was discovered that the level of nitrate and nitrite ions is surpassed not only in aquatic bodies, but also in the Republic of Kazakhstan’s atmospheric air and soil. Furthermore, there was a decline in aquatic organism diversification and abundance in the analyzed water bodies, which could be attributed to nitrate-nitrite pollution and harmful effects on juveniles. As a result, the goal of this study was to look at the effects of nitrates and nitrites on Danio Rerio embryogenesis. This object was chosen over others for its lower maintenance expenses, rapid advancement of embryogenesis phases, transparency, and the comparatively small size of the embryos for successful visual observation. Based on our findings, the embryotoxic and teratogenic effects of calcium nitrate and sodium nitrite have been proven, resulting in the death of fish. Calcium nitrate and sodium nitrite at concentrations of 1, 10, and 100 MPC have been demonstrated to cause dose-dependent embryonic death. Furthermore, to a greater extent under the action of sodium nitrite. Teratogenic diseases were discovered in surviving larvae, including edema of the yolk sac and pericardium of the heart, curvature of the skeleton and asymmetry of the body, edema of the retina, and aberrant formation of the organs of the oral cavity. The findings acquired are theoretically and practically important in the fields of ecology, ecotoxicology, and aquatic organism biodiversity protection. They contribute to our understanding of the hazardous effects of naturally occurring nitrates and nitrites, as well as the need to employ Danio rerio embryos and larvae as test objects for bioindication of polluted water bodies.